The Role of Planning in Delivering Low-Carbon Urban Infrastructure. (August 2013) - Williams, Joanna
Cities are the single largest contributor to climate change. Thus it is important that, where possible, low-carbon infrastructure is integrated into cities to try to reduce CO2 emissions. Planning (plans, policy, and process) can encourage this. In this paper international best practice is drawn upon to explore a range of planning approaches—collaborative, systemic, and market shaping—that have been used to introduce low-carbon infrastructure into cities. A new typology is developed and the strengths and weaknesses of planning approaches are evaluated. The importance of context in the success of each approach is highlighted and suggestions are made for the circumstances in which each may be most effectively employed, while exploring how planning can be used to provide a 'protected space' in which low-carbon systems can develop.